Pathologically confirmed brain metastases from primary uterine cervical tumors: two cases and a literature review - Yalan Bi; Lei Li (World Journal of Surgical Oncology, 2019)
Abstract Background Pathologically confirmed brain metastasis from primary cervical cancer is extremely rare. Herein, we report two cases of intracranial metastasis from cervical cancer that were histopathologically confirmed after surgical excision. In addition, we conducted a literature review to characterize the clinical manifestation, pathogenesis, and treatment of these patients. Case summary Among the 1800 patients with primary cervical cancer who received therapy at our center from 2010 to 2018, two patients (0.1%) had definite histopathological evidence of brain metastasis. A 46-year-old female who had a history of poorly differentiated stage IIB cervical cancer with neuroendocrine differentiation presented with a solitary mass in the right occipital lobe 26 months after the initial diagnosis. She underwent surgery and chemotherapy but died of disease progression 9 months later. Another 55-year-old female diagnosed with poorly differentiated stage IVB cervical squamous cancer presented with a solitary mass in the right frontal lobe 16 months after simple hysterectomy. Twelve months later, multiple lesions were observed in the bilateral frontal-parietal lobe. The lesions were treated by surgery and stereotactic radiosurgery. The patient died of multiple organ failure 14 months later. Conclusion The pathogenesis and best management of brain metastasis from cervical cancer are not clear. Highly invasive subtypes or advanced cancer stages may be the key clinicopathological factors of brain metastasis. Surgical treatment is warranted in patients with a good health status and without metastasis to other sites.